Proceedings of IGARSS '94 - 1994 IEEE International Geoscience and Remote Sensing Symposium
DOI: 10.1109/igarss.1994.399253
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal effect of internal waves on the ocean surface

Abstract: The effects of nonlocal connection between an internal wave field and centimeter-and decimeter-scale waves were studied using the JUSREX-92 data. Centimeter-scale wave parameters were measured by means of a ship-mounted, X-band side-looking radar, decimeter-scale wave parameters were measured with a two-dimensional optical device (the wave spectrum analyzer) and parameters of the internal waves were measured by a towed, profiling batfish operated by the Atlantic Division of the Shirshov Institute of Oceanology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…[37] The account of SW nonlinearity allows constructing of the uniformly valid stationary solutions to the problem of the SW -IW interaction in the vicinity of their group velocity resonance and to describe a number of observed experimental effects. The basic properties of the solution correspond to the results of observations of SW modulations by large amplitude internal waves [Kropfli et al, 1999;Bakhanov and Ostrovsky, 2002] and by the relatively short internal waves [Basovich et al, 1987;Bakhanov et al, 1994].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…[37] The account of SW nonlinearity allows constructing of the uniformly valid stationary solutions to the problem of the SW -IW interaction in the vicinity of their group velocity resonance and to describe a number of observed experimental effects. The basic properties of the solution correspond to the results of observations of SW modulations by large amplitude internal waves [Kropfli et al, 1999;Bakhanov and Ostrovsky, 2002] and by the relatively short internal waves [Basovich et al, 1987;Bakhanov et al, 1994].…”
Section: Discussionsupporting
confidence: 69%
“…This means that the relatively long SW ( c < 1/2), after crossing the region of internal wave current, keeps the low frequency amplitude modulations. That property is confined by field measurements [ Basovich et al , 1987; Bakhanov et al , 1994].…”
Section: Stokes Surface Wave Resonantly Modulated By the Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) Forerunner of internal waves. A significant number of experiments (see Basovich et al 1987;Bakhanov et al 1994) demonstrated surface wave anomalies at an extended distance (about 1 km) from the regions where internal waves exist, that is IW forerunner arises. Significant sea surface anomalies can be observed ahead of an IW train.…”
Section: Introductionmentioning
confidence: 99%
“…(iv) No uniformity in SW space modulations. Spectral density variations may have a characteristic period that is shorter than that of periodic IWs (see Basovich et al 1987;Bakhanov et al 1994). The SW spectral density along a uniform periodic IW train grows on average from the train's end to its head; the spectral density of decimetre-length SWs at the train head can exceed several times the unperturbed value.…”
Section: Introductionmentioning
confidence: 99%